2009
DOI: 10.1007/s00454-009-9180-4
|View full text |Cite
|
Sign up to set email alerts
|

Very Colorful Theorems

Abstract: We prove several colorful generalizations of classical theorems in discrete geometry. Moreover, the colorful generalization of Kirchberger's theorem gives a generalization of the theorem of Tverberg on non-separated partitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 5 publications
0
53
0
Order By: Relevance
“…There are examples showing that it is not sufficient that the convex hulls of triples contain the origin, but weaker relaxations are possible [274]. Arocha et al [29] also proved another "very colorful Carathéodory theorem".…”
Section: Carathéodorymentioning
confidence: 99%
“…There are examples showing that it is not sufficient that the convex hulls of triples contain the origin, but weaker relaxations are possible [274]. Arocha et al [29] also proved another "very colorful Carathéodory theorem".…”
Section: Carathéodorymentioning
confidence: 99%
“…For the Colorful Carathéodory Theorem, the assumption of centeredness can be replaced by a weaker assumption (see, for example, [2,3,13,20]). This prompts the following question.…”
Section: Proof By Construction the Avoiding Complexmentioning
confidence: 99%
“…, C d } is called a colorful configuration. We call C centered if 0 ∈ relint conv(C i ) for all 0 ≤ i ≤ d. The assumption that C is centered can be considerably weakened (see, for example, [2,3,13,20]) but in this paper we will only consider centered configurations; see Question 1. We call a subset S ⊆ i C i a colorful simplex if |S ∩ C i | ≤ 1 for all i and we call the simplex S hitting if dim S = |S| − 1 = d and 0 ∈ conv(S).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, two independent groups have observed that these hypotheses can be weakened a bit more; namely, it suffices that the union of pairs of colours captures the point: Theorem 4 (Arocha et al [1], Holmsen et al [11]…”
Section: Introductionmentioning
confidence: 99%